Prognostic Impact of Metastatic Site and Pattern in Patients with Metastatic Head and Neck Cancer. (24th October 2020) - Bollig, Craig A.; Newberry, Christopher I.; Galloway, Tabitha L. I.; Zitsch, Robert P.; Hanly, Elyse K.; Zhu, Vivian L.; Pagedar, Nitin; Nallani, Rohit; Bur, Andres M.; Spanos, William C.; Jorgensen, Jeffrey B.
Abstract : Objectives/Hypothesis: Investigate the relationship between site and pattern of distant metastasis (DM) and overall survival (OS) in a multi‐institutional cohort of patients with DM head and neck cancer (HNC). Study Design: Retrospective review. Methods: 283 patients treated at 4 academic centers in the Midwest HNC Consortium between 2000 and 2015 were retrospectively reviewed. Disease patterns were divided between solitary metastatic versus polymetastatic (≥2 sites) disease. Survival functions for clinically relevant variables were estimated using Kaplan‐Meier and Cox proportional hazards models. Results: Median OS for all patients was 9.0 months (95% confidence interval [CI]: 7.4–10.6). Lung (n = 220, 77.7%) was the most common site of DM, followed by bone (n = 90, 31.8%), mediastinal lymph nodes (n = 55, 19.4%), liver (n = 41, 14.5%), and brain (n = 17, 6.0%). Bone metastases were independently associated with the worst prognosis (hazard ratio [HR] = 1.6, 95% CI: 1.3–2.1). On univariate analysis, brain metastases were associated with improved prognosis (HR = 0.5, 95% CI: 0.3–0.9), although this was not statistically significant on the multivariate analysis. Polymetastatic disease was present in the majority of patients (n = 230, 81.3%) and was associated with a worse prognosis compared to solitary metastatic disease (HR = 1.4, 95% CI: 1.0–2.0). Conclusion: Our large, multi‐institutional review indicates that both the metastatic pattern and site of DM impact OS. Polymetastatic disease and bone metastasis are associated with worse prognosis, independent of treatment received. Level of Evidence: 4 Laryngoscope, 131:E1838–E1846, 2021